Reading Habits of students at UiTM Sarawak / Rasidah Mahdi … [et.al.]. - Mahdi, Rasidah; Unin, Norseha; Saili, Abdul Rahman (2017)
This study employed a quantitative research method to investigate reading habits of college students at Universiti Teknologi MARA (UiTM) Sarawak. A total of 400 (108 male and 292 female) students voluntarily participated in the study by completing a self-reported survey. Descriptive analysis indicated that 235 (58.8%) of them are Forced Readers, 91 (22.8%) are Reluctant Readers, 42 (10.5%) are Avid Readers, 29 (7.3%) are Marginal Readers, and 3 (0.8%) are Non-Readers. The preference for reading softcopy materials is more evident among them, but not for the avid readers. The hours spent on reading are equivalent to 27 books per year. Although a high percentage (87.5%) agreed that they read to complete their assignments, more than 70% agreed that they read because of interesting contents. This high percentage of respondents who agreed with reading interesting contents, especially among Avid Readers (85.7%) is a positive indication. The most preferred language for academic reading is English.